2023
DOI: 10.3390/antiox12071461
|View full text |Cite
|
Sign up to set email alerts
|

Pepper Fruit Extracts Show Anti-Proliferative Activity against Tumor Cells Altering Their NADPH-Generating Dehydrogenase and Catalase Profiles

Marta Rodríguez-Ruiz,
María C. Ramos,
María J. Campos
et al.

Abstract: Cancer is considered one of the main causes of human death worldwide, being characterized by an alteration of the oxidative metabolism. Many natural compounds from plant origin with anti-tumor attributes have been described. Among them, capsaicin, which is the molecule responsible for the pungency in hot pepper fruits, has been reported to show antioxidant, anti-inflammatory, and analgesic activities, as well as anti-proliferative properties against cancer. Thus, in this work, the potential anti-proliferative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The prolonged exposure to low temperatures might activate the enzymatic AO system in pepper fruits to respond to physiological stress by increasing the activities of SOD, CAT, and POD [10]. Rodríguez-Ruiz et al [5] reported that CAT activity in pepper fruit is higher than that of SOD and POD due to the modulation of the CAT gene and its activities during the fruit ripening and senescence process. Among the tested samples, the MT-treated samples displayed slightly higher AO enzyme activity.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged exposure to low temperatures might activate the enzymatic AO system in pepper fruits to respond to physiological stress by increasing the activities of SOD, CAT, and POD [10]. Rodríguez-Ruiz et al [5] reported that CAT activity in pepper fruit is higher than that of SOD and POD due to the modulation of the CAT gene and its activities during the fruit ripening and senescence process. Among the tested samples, the MT-treated samples displayed slightly higher AO enzyme activity.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…The primary cause of pepper fruit softening is its cell wall polysaccharides, and certain enzymes that hydrolyze the cell wall-like PG, PME, pectin lyases (PLs), β-galactosidases (β-Gals), endo-1, and 4-β-D-glucanases (EGases)-become extremely active and negatively alter the texture of the pepper fruits [4]. Furthermore, pepper fruit deterioration due to its weakened stress response system has also been widely reported, as shown by decreased activity of AO enzymes such as SOD, POD, and CAT, which are the robust antioxidant systems in plants that effectively slow down the senescence process [5]. Proper storage is crucial for preserving the freshness of green pepper fruits for extended periods.…”
Section: Introductionmentioning
confidence: 99%